2017
DOI: 10.1200/jco.2017.35.15_suppl.e18211
|View full text |Cite
|
Sign up to set email alerts
|

Oncology guidelines usage in a low and middle-income country.

Abstract: e18211 Background: Healthcare providers often rely on clinical practice guidelines to help inform and optimize patient care. However, most of these guidelines are from reputable organizations that are based in developed countries. There is a paucity of data about the status of guidelines in low and middle-income countries (LMIC), specifically in terms of their availability, usage and quality. Objective: To determine utilization of oncology guideline and potential barriers to usage in a LMIC among clinical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 4 publications
0
21
0
Order By: Relevance
“…It did not include payments related to meals, transportation and accommodation, stock ownership, investment interest or payments from medical device companies, as is complied in the US’s Open Payments Data 30. The CPG authors strongly influence oncology practice, both in the USA and internationally32 by recommending treatment algorithms. They may well be identified as prime targets for representatives of pharma attempting to promote the sale of their anticancer products.…”
Section: Discussionmentioning
confidence: 99%
“…It did not include payments related to meals, transportation and accommodation, stock ownership, investment interest or payments from medical device companies, as is complied in the US’s Open Payments Data 30. The CPG authors strongly influence oncology practice, both in the USA and internationally32 by recommending treatment algorithms. They may well be identified as prime targets for representatives of pharma attempting to promote the sale of their anticancer products.…”
Section: Discussionmentioning
confidence: 99%
“…The 15 included studies comprised three interviewbased qualitative studies [53][54][55], two studies that utilized qualitative and quantitative methods, and presented results of each method separately [53,56], and 11 quantitative studies all using surveys [15,[57][58][59][60][61][62][63][64][65][66]. Most studies were from Australia (n = 5) [58,59,61,65,66] or Canada (n = 4) [15,54,56,57].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Three studies were published in the 1990s [59,62,65], two in the 2000s [15,61], and ten from 2010 to 2019 [53-58, 60, 63, 64, 66]. It is also worth noting that only one study focused on CPG implementation in low-and middle-income countries, concluding that while awareness of cancer CPGs was high among clinicians, CPG implementation was limited by inadequate facilities and CPGs that were overly complex and not applicable to the local context [63]. The remaining studies were situated in high income countries (Table 4).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…• Adult Cancer Pain • Antiemesis (nausea and vomiting prevention) )-which were downloaded more than 10 million times across the world in 2018-are already being used by 90% of radiation oncologists in Nigeria, according to a study published in the Journal of Global Oncology on April 11, 2018. 3 But the study also found some clinicians can have difficulty implementing the recommendations due to facility resource limitations. The NCCN Harmonized Guidelines are helping to address that problem by including two tiers of treatment recommendations, which vary depending on access to resources like radiation equipment or laparoscopic surgical tools.…”
mentioning
confidence: 94%